Association of whole grains intake and the risk of digestive tract cancer: a systematic review and meta-analysis - Zhang, Xiao-Feng; Wang, Xiao-Kai; Tang, Yu-Jun; Guan, Xiao-Xian; Guo, Yao; Fan, Jian-Ming; Cui, Ling-Ling (Nutrition journal, 2020)
Several epidemiological studies have investigated the association between whole grains intake and digestive tract cancer risk; however, the results are still controversial. The purpose of this meta-analysis was to assess the association. Studies published before March 2020 were searched in database and other sources. The risk ratio (RR) with the 95% confidence interval (CI) were pooled using fix or random-effects models. This meta-analysis included 34 articles reporting 35 studies, 18 studies of colorectal cancer, 11 studies of gastric cancer and 6 studies of esophagus cancer, involving 2,663,278 participants and 28,921 cases. Comparing the highest-intake participants with the lowest-intake participants for whole grains, we found that the intake of whole grains were inversely related to colorectal cancer (RR = 0.89, 95% CI: 0.84-0.93, P < 0.001), gastric cancer (RR = 0.64, 95% CI: 0.53-0.79, P < 0.001), esophagus cancer (RR = 0.54, 95% CI: 0.44-0.67, P < 0.001), respectively. However, subgroup analysis of colorectal cancer found no significant association in the case-control studies and studies of sample size < 500, and subgroup analysis of gastric cancer found no significant association in the cohort studies and studies of American population. No study significantly affected the findings in the sensitivity analysis. No publication bias was found in the studies for colorectal cancer and esophagus cancer except in the studies for gastric cancer. This meta-analysis provides further evidence that whole grains intake was associated with a reduced risk of digestive tract cancer. Our result supports the dietary guidelines that increase whole grains intake to reduce the risk of digestive tract cancer.